The talent lab. The secrets of creating and sustaining success - Slot, O.; Timson, S.; Warr, C. (Penguin Random House, 2017)
Simon Timson and Chelsea Warr were the Performance Directors of UK Sport, tasked with the outrageous objective of delivering even greater success to Team GB and ParalympicsGB at Rio than in 2012. Something no other host nation had ever achieved in the next Games.